Post-COVID-19 Gastro-Intestinal Disturbances - Scarpellini, Emidio; Tack, Jan (Reviews on Recent Clinical Trials, 2023)
Background: Since the end of 2019, SARS-CoV-2 has been responsible for the multisystemic hyper-inflammatory disease, namely, COVID-19, as a majorly impactful pandemic. Gastrointestinal (GI) symptoms occurring during and after disease are gaining increasing attention among experts. Methods: We briefly review and comment on preliminary and recent evidences on prevalence, pathophysiology, and perspective treatment options for GI disturbances during and after COVID-19. Results: Several reports from the literature show a significant portion of COVID-19 patients suffering from GI symptoms both at the early stages of the disease and after the end of it, sometimes for several months, namely “long-COVID-19” patients, irrespective of vaccination. An unsolved issue regarding COVID-19 is the association between GI symptoms and the outcome of COVID-19 patients. Several studies and metanalyses suggest a worse evolution of COVID-19 in patients presenting with GI symptoms. However, these data have not been agreed. Indeed, only one uniform observation can be found in the literature: patients with chronic liver disease have a worse outcome from COVID-19 infection. Upper and lower GI symptoms have similarities with postinfectious functional dyspepsia (FD) and irritable bowel syndrome (IBS). FD and IBS following infection are recognize as pathophysiological factor the gut microbial, which is a gut microbial quali- and quantitative unbalance, namely dysbiosis. Furthermore, several preliminary reports and ongoing clinical trials have shown gut microbiota modulation by pre-, pro- and postbiotics to be effective in changing and preventing COVID-19 natural course. Conclusion: GI symptoms characterize both long- and non-long-COVID-19 with a potentially significant impact on its natural course. Gut microbiota modulation seems to be a sensible target for disease treatment and/or prevention.
Keywords: gut microbiota